Estimations of high-temperature diffusion in Chernobyl’s concrete construction - Dikiy, N.P.; Dedik, A.N.; Dovbnya, A.N.; Uvarov, V.L. (Вопросы атомной науки и техники, 2005)
The content of isotopes Ti, Ni, Zr, Cs and U in the cores, which was taken from the concrete construction of ChAPS, was studied by the gamma-activation analysis. It has been developed a numerical model to analyze heat and mass transfer in concrete at high temperatures accompanying incident of 1986. Comparison of the measured isotope distributions with the simulation data has enabled to estimate some attendant circumstances of the incident.